The Artistic Structure of Arabic Poetry in the Works of Antarah ibn Shaddad Al-Abdusi - Suleiman, Sabah Hawil (Al-Mukhtar Journal of Social Sciences, 2024)
Tanakul, a form of poetry in the Arab tradition, played a significant role in the works of Antarah ibn Shaddad Al-Abdusi. It encompassed various literary devices, including historical references that influenced the poet's compositions. The comprehensive poetic approach in studying poetic texts examined both the language used by the poet and the thematic elements employed. Antarah's poetry, particularly known for its lyrical nature, adhered to artistic traditions while showcasing his own unique style. His verses not only depicted romantic narratives but also expressed his emotions and thoughts beyond conventional themes such as riddles, pride, and elegies. Antarah's poetry served as a reflection of political and social life during the pre-Islamic era, capturing the essence of bravery and showcasing his creative prowess. Although this analysis does not cover all aspects comprehensively, it highlights Antarah's contributions in producing authentic poetry through meticulous writing, precise language, and coherent ideas.
Keywords: Tanakul; Antarah ibn Shaddad; Lyrical poetry